The impact of money service businesses on monetary policy objectives for the period 1989-1998 - Fletcher, Gem ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Explores the implications of the operations of the Money Services Businesses (MSBs) on the effectiveness of the monetary policy measures of the Central Bank in influencing the intermediate targets of investment and exchange rate stability as well as the overall objectives of steady economic growth and domestic price stabilityl